Δ15N patterns in three subtropical estuaries show switch from nitrogen "reactors" to "pipes" with increasing degradation. (19th November 2018) - Wells, Naomi S.; Eyre, Bradley D.
Abstract: Ongoing alterations to estuaries by inland agricultural intensification and coastal development could affect their capacity to regulate the flux of excess terrestrial nitrogen (N) to the coastal ocean. Here, a new multiform δ 15 N metric was developed to measure how "pristine, " moderately impacted, and highly degraded estuaries recycle (assimilation, mineralization) and remove (denitrification, anaerobic ammonium oxidation) N. Organic (dissolved and particulate, δ 15 N and δ 13 C) and inorganic (nitrate and ammonium, δ 15 N and δ 18 O) N forms were measured over the salinity gradient in the wet and dry season in subtropical estuaries receiving increasing terrestrial N loads (pristine: 16 kg N d −1, moderate: 150 kg N d −1, degraded: 630 kg N d −1 ). The difference in the inorganic vs. organic pool δ 15 N composition increased between the pristine (0 ± 2‰), moderate (10 ± 6‰), and degraded (20 ± 8‰) systems, indicating that N recycling decreased as degradation increased. The N2 O concentrations, NO3 − dual isotope values, and offsets between "measured" and "mixing expected" δ 15 N values further revealed that microbial processes removed up to 30% of the N load entering the moderately degraded estuary, but only 9% in the highly degraded estuary. Hydrologic differences (depth and flushing times [FTs]) could not fully explain these shifts in N fate between the estuaries and seasons, which instead aligned with nonlinear increases in phytoplankton biomass and light penetration with increasing N loads. These isotopic indicators provide direct evidence that estuaries switch from "reactors" that assimilate and remove terrestrial N to "pipes" that transport N directly to sea as degradation increases.